2006
DOI: 10.1073/pnas.0605389103
|View full text |Cite
|
Sign up to set email alerts
|

Engineering cottonseed for use in human nutrition by tissue-specific reduction of toxic gossypol

Abstract: Global cottonseed production can potentially provide the protein requirements for half a billion people per year; however, it is woefully underutilized because of the presence of toxic gossypol within seed glands. Therefore, elimination of gossypol from cottonseed has been a long-standing goal of geneticists. Attempts were made to meet this objective by developing so-called ''glandless cotton'' in the 1950s by conventional breeding techniques; however, the glandless varieties were commercially unviable because… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
269
0
6

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 402 publications
(275 citation statements)
references
References 40 publications
0
269
0
6
Order By: Relevance
“…Diploid cotton species share a common chromosome number (n = 13), and high levels of synteny or colinearity are observed among them [9][10][11][12] . The tetraploid cotton species (2n = 4× = 52), such as G. hirsutum L. and Gossypium barbadense L., are thought to have formed by an allopolyploidization event that occurred approximately 1-2 million years ago, which involved a D-genome species as the pollen-providing parent and an A-genome species as the maternal parent 13,14 . To gain insights into the cultivated polyploid genomes-how they have evolved and how their subgenomes interact-it is first necessary to have a basic knowledge of the structure of the component genomes.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…Diploid cotton species share a common chromosome number (n = 13), and high levels of synteny or colinearity are observed among them [9][10][11][12] . The tetraploid cotton species (2n = 4× = 52), such as G. hirsutum L. and Gossypium barbadense L., are thought to have formed by an allopolyploidization event that occurred approximately 1-2 million years ago, which involved a D-genome species as the pollen-providing parent and an A-genome species as the maternal parent 13,14 . To gain insights into the cultivated polyploid genomes-how they have evolved and how their subgenomes interact-it is first necessary to have a basic knowledge of the structure of the component genomes.…”
Section: A R T I C L E Smentioning
confidence: 99%
“…Transgenic technology has also been employed to produce new valuable germplasms. By seed-specific suppression of the CDN expression, plants of ultra-low gossypol cottonseed (ULGCS) were developed (Sunilkumar et al, 2006), and field trial results confirmed the stability and specificity of the ULGCS trait, suggesting that this RNAi-based product has the potential to be commercially viable (Palle et al, 2013).…”
Section: Genetic Engineering Of Gossypol Traitsmentioning
confidence: 94%
“…It is planted in more than 80 countries by about 20 million farmers, and occupies approximately 5% of the world's arable land (Sunilkumar et al, 2006;Wang et al, 2012). Branching pattern is an important agronomic trait of cotton, and understanding the molecular basis of cotton branching will help develop compact cotton varieties that are suitable for mechanized harvesting, through the modulation of the plants' architecture.…”
Section: Discussionmentioning
confidence: 99%